ANALISIS FAKTOR YANG MEMENGARUHI HUBUNGAN SEKSUAL PADA LANJUT USIA (LANSIA) WANITA DI WILAYAH KERJA PUSKESMAS TANAH LUAS KABUPATEN ACEH UTARA TAHUN 2013 - Novi Zuhra; Abdul Jalil Amri Arma; Asfriyati . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
ABSTRACT As the aging process running, the ability of elderly sexuality generally will decrease, so it is necessary to review of sexual problems of the elderly. In fact, not all of the elderly can experience a harmonious sexual life, there are many factors that influence sexual intercourse in the elderly . Type of the research is descriptive using a method of applying explanatory factor analysis recearch where entire 1200 people elderly population aged over 60 years old in the Work Land Area of Community Health Center in North Aceh district. While the sample used in this study amounted to 105 elderly. Based on the result of research, there are 9 (nine) variables that influence sexual intercourse in the elderly (education, age, knowledge, disease, taboos, culture, attractiveness, anxiety, and boredom) when analyzed formed two (2) factors that influence sexual intercourse advanced age is factor 1 (first) is composed of variable knowledge, disease, age, culture and education, called the characteristic factor. And  factor 2 (second) consists of variable attractiveness, taboo, anxiety and boredom called psychological factors. Based on the results of the research can be suggested to improve the knowledge of the elderly, by spreading out information about sexuality and reproductive health characteristics based on the factors and psychological factors so that made positive attitude towards sexuality in order to maintain harmony in family . Keywords  : factor analysis, sexual intercourse, elderly